Spatial econometrics and GIS YouTube playlist - Mark L. Burkey (REGION, 2018)
This resource describes a website and playlist of YouTube videos using open source software (R, GeoDa, and QGIS) designed to help get scholars up and running with analyzing their own data. In the series sample data, handouts, code, and map files are provided. The course covers the basics of integrating data into a spatial data set, contiguity and spatial correlation, doing basic spatial regressions in GeoDa, and doing more sophisticated specification tests and regressions in R.
Keywords: 330; spatial econometrics; instructional videos